The Gold Standard in Ecuador, 1898 - 1932 - Naranjo, Marco (2020)
The present study makes a succinct explanation of the conceptual characteristics of the monetary regime of the Gold Standard and its application in Ecuador for the periods 1898 - 1914 and 1925 - 1932. Above all, it tries to show the effects generated by this monetary system on stability and economic growth in this Andean nation of South America.